Novel drug developmental strategies for treatment‐resistant depression. (26th January 2022) - Borbély, Éva; Simon, Mária; Fuchs, Eberhard; Wiborg, Ove; Czéh, Boldizsár; Helyes, Zsuzsanna
Abstract : Major depressive disorder is a leading cause of disability worldwide. Because conventional therapies are ineffective in many patients, novel strategies are needed to overcome treatment‐resistant depression (TRD). Limiting factors of successful drug development in the last decades were the lack of (1) knowledge of pathophysiology, (2) translational animal models and (3) objective diagnostic biomarkers. Here, we review novel drug targets and drug candidates currently investigated in Phase I–III clinical trials. The most promising approaches are inhibition of glutamatergic neurotransmission by NMDA and mGlu5 receptor antagonists, modulation of the opioidergic system by κ receptor antagonists, and hallucinogenic tryptamine derivates. The only registered drug for TRD is the NMDA receptor antagonist, S ‐ketamine, but add‐on therapies with second‐generation antipsychotics, certain nutritive, anti‐inflammatory and neuroprotective agents seem to be effective. Currently, there is an intense research focus on large‐scale, high‐throughput omics and neuroimaging studies. These results might provide new insights into molecular mechanisms and potential novel therapeutic strategies. Abstract :